Syntheses and crystal structures of three triphenylsulfonium salts of manganese(II), iron(III) and cobalt(II) - Waylan Callaway; Matthew Elterman; Nikita Krasilnikov; Gavin Roberts; Davis Rutan; Ty Spencer; Clifford W. Padgett; Will E. Lynch (Acta Crystallographica Section E: Crystallographic Communications)
Bis(triphenylsulfonium) tetrachloridomanganate(II), (C18H15S)2[MnCl4] (I), triphenylsulfonium tetrachloridoferrate(III), (C18H15S)[FeCl4] (II), and bis(triphenylsulfonium) tetrachloridocobaltate(II), (C18H15S)2[CoCl4] (III), crystallize in the monoclinic space groups P21/n [(I) and (III)] and P21/c [(II)]. Compounds (I) and (III) each contain two crystallographically independent triphenylsulfonium (TPS+) cations in the asymmetric unit, whereas (II) has one. In all three compounds, the sulfonium centers adopt distorted trigonal–pyramidal geometries, with S—C bond lengths falling roughly in the 1.78–1.79 Å range and C—S—C angles observed at about 101 to 106°. The [MCl4]n− anions (M = Mn2+, Fe3+, Co2+; n = 2,1,2) adopt slightly distorted tetrahedral geometries, with M—Cl bond lengths in the 2.19–2.38 Å range and Cl—M—Cl angles of approximately 104–113°. Hirshfeld surface analyses shows that H...H and H...C contacts dominate the TPS+ cation environments, whereas H...Cl and short M—S interactions link each [MCl4]n− anion to the surrounding cations. In (I) and (III), inversion-centered π–π stacking further consolidates the crystal packing, while in (II) no π–π interactions are observed.